Automated synthesis of quantum dot nanocrystals by hot injection: Mixing induced self-focusing - Salaheldin, Ahmed M.; Walter, Johannes; Herre, Patrick; Levchuk, Ievgen; Jabbari, Yasaman; Kolle, Joel; Brabec, Christoph; Peukert, Wolfgang; Segets, Doris (Chemical Engineering Journal, 2017)
The hot injection technique for the synthesis of quantum dots (QDs) is a well-established and widely used method in the lab. However, scale-up rules do not exist. One reason is that in particular the role of process parameters like mixing on particle formation is largely unknown, as systematic examination of the latter is impossible for the laborious and complex manual synthesis. Herein we studied the mixing induced self-focusing of particle size distributions (PSDs) of CdSe QDs using automation in combination with a defined stirrer geometry. Basis for our study is a platform that allows parallelization with inline temperature monitoring, defined injection rate, accurate sampling times as well as controlled stirring. Reproducibility in terms of optical product properties was analyzed by absorption and emission whereas reproducibility in terms of the PSD was verified by deconvolution of UV/Vis absorbance spectra and especially by analytical ultracentrifugation (AUC) complemented by transmission electron microscopy (TEM). In line with previous results, AUC confirmed that even QDs made by hot injection in an automated setup are polydisperse with multimodal size distributions. Finally, reproducibility in combination with early stage sampling and controlled mixing allowed us for the first time to analyze the influence of stirring on focusing and defocusing of PSDs, that has been expressed in terms of the evolution of the relative standard deviation (RSD). Our work paves the way to gain in-depth understanding of often forgotten process-structure relationships of colloidal nanoparticles which eventually is a first step in the direction of the development of scalable synthesis and reliable application of high-quality QDs in technical application

Cleaning matters! - Mahmoud, Ahmed Salaheldin Abdelhamid; Segets, Doris (ACS Combinatorial Science, 2019)
Translation of a manual process to high throughput for research and development requires special consideration. One important and often unreported aspect is the establishment of an efficient cleaning routine. This becomes significant, as precious time and in particular material would be lost, i.e., when low-quality high throughput experimentation is involved. We present a fully automated cleaning routine of the challenging synthesis of cadmium selenide quantum dots. Manual, semi-automated and fully automated cleaning protocols were executed and compared in terms of spectral similarities of the synthesized colloids. Only the fully automated protocol enabled true 24/7 operation.
CRIS-Team Scopus Importer:2019-10-18
Keywords: Automation; Cleaning; High throughput experimentation; Nanocrystals; Quantum dots

Controlled mixing during colloidal quantum dot synthesis: A proxy-concept based on equivalent parameters - Salaheldin, Ahmed M.; Segets, Doris (Chemical Engineering Journal, 2023)
Mixing is a key process parameter during liquid phase particle synthesis that requires special attention, in particular for scalable process and reactor development. This issue is especially pressing for advanced materials where on the one hand multifunctional properties require products of utmost quality, while on the other hand only few strategies for process design are yet developed. One material class in this context is quantum dot (QD) nanocrystals. By making use of automation and high throughout (HT) experimentation, we could recently demonstrate qualitatively the role of mixing on focusing and defocusing during QD synthesis by hot injection. In this work, we demonstrate the application of HT methodologies to investigate the effect of mixing as an important process parameter during process optimization and scale up. We performed reaction optimization by screening a multi-parameter design space using design of experiments (DoE) and machine learning (ML). We developed a so-called cold model as proxy that is based on equivalent mixing times (EMTs) derived from a competing parallel reaction system. Experimentally, we realized a fully automated approach using a HT platform for particle synthesis. The final dataset (128 experiments for model development including repeats and 29 experiments for prediction testing) was combined with DoE and complimented with machine learning. By doing so, with DoE, we could reduce the number of experiments required to develop a predictive, statistical knowledge base for EMTs at ambient conditions. Finally, we demonstrated the applicability of EMTs for two defined stirrer geometries to fine tune the widths of the particle size distribution and photoluminescence of QDs at increasing reaction volumes from 20 mL to 80 mL. This opens the door towards scalable processes for QDs at increased reaction volumes while maintaining product quality.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Design of experiments; High-throughput experimentation; Hot injection; Machine learning; Mixing time; Quantum dots

Interplay between size, morphology, microstructure defects and optoelectronic properties of CdSe nanocrystals - Neumann, S.; Rudolph, M.; Menter, Christina; Mahmoud, Ahmed Salaheldin Abdelhamid; Segets, D.; Rafaja, D. (ACTA CRYSTALLOGRAPHICA A-FOUNDATION AND ADVANCES, 2021)
CRIS-Team WoS Importer:2022-04-01

Microstructure characteristics of non-monodisperse quantum dots: On the potential of transmission electron microscopy combined with X-ray diffraction - Neumann, Stefan; Menter, Christina; Mahmoud, Ahmed Salaheldin Abdelhamid; Segets, Doris; Rafaja, David (Crystengcomm, 2020)
Although the concept of quantum confinement was introduced more than thirty years ago, a wide application of quantum dots is still limited by the fact that monodisperse quantum dots with controlled optoelectronic properties are typically synthesized on a relatively small scale. Larger scale synthesis techniques are usually not able to produce monodisperse nanoparticles yet. In this contribution, we illustrate the capability of the combination of transmission electron microscopy and X-ray diffraction to reveal detailed and scale-bridging information about the complex microstructure of non-monodisperse quantum dots, which is the first step towards further upscaling of the techniques for production of quantum dots with controlled properties. As a model system, CdSe quantum dots synthesized using an automated robotic hot-injection method at different temperatures were chosen. The combined microstructure analytics revealed the size and shape of the CdSe nanocrystals and the kind, density and arrangement of planar defects. The role of the planar defects in the particle coarsening by oriented attachment and the effect of the planar fault arrangement on the phase constitution, on the crystallographic coherence of the counterparts and on the optoelectronic properties are discussed.
CRIS-Team Scopus Importer:2020-06-09

Rapid Characterization and Parameter Space Exploration of Perovskites Using an Automated Routine - Reinhardt, Elisabeth; Salaheldin, Ahmed M.; Distaso, Monica; Segets, Doris; Peukert, Wolfgang (ACS Combinatorial Science, 2020)
Hybrid, e.g., organic inorganic, perovskites from the type methylammonium lead iodide CH3NH3PbI3 are promising solar cell materials. However, due to the large parameter space spanned by the manifold combinations of divalent metals with organic cations and anions, an efficient approach is needed to rapidly test and categorize new promising materials. Herein, we developed a high throughput approach for the automated synthesis of perovskite layers with different precursor ratios at varying annealing temperatures. The layers were analyzed by optical absorption and photo-luminescence (PL) spectroscopy as well as X-ray diffraction (XRD) and evaluated using two different procedures. The first one is a stepwise exclusion of nonperforming reactant ratios and synthesis conditions by using both spectroscopic techniques, followed by a final validation of the procedure by XRD. In the second procedure, only PL results were consulted in combination with high throughput screening using design of experiments (DoE) to reduce the total number of experiments needed and compared to the manual cascade approach. Noteworthy, by simple PL screening, it was possible to identify the best ratio of perovskite to byproducts and annealing temperature. Thus, only with PL, more detailed results as with the manual protocol were reached, while at the same time the effort for characterization was significantly reduced (by 60% of the experimental time). In conclusion, our approach opens a way toward fast and efficient identification of new promising materials under different reaction and process conditions.
CRIS-Team WoS Importer:2020-01-31